Double-Layer Magnetic Nanoparticle-Embedded Silica Particles for Efficient Bio-Separation - Kyeong, San; Jeong, Cheolhwan; Kang, Homan; Cho, Hong-Jun; Park, Sung-Jun; Yang, Jin-Kyoung; Kim, Sehoon; Kim, Hyung-Mo; Jun, Bong-Hyun; Lee, Yoon-Sik (PUBLIC LIBRARY SCIENCE, 2015)
Superparamagnetic Fe3O4 nanoparticles (NPs) based nanomaterials have been exploited in various biotechnology fields including biomolecule separation. However, slow accumulation of Fe3O4 NPs by magnets may limit broad applications of Fe3O4 NP-based nanomaterials. In this study, we report fabrication of Fe3O4 NPs double-layered silica nanoparticles (DL MNPs) with a silica core and highly packed Fe3O4 NPs layers. The DL MNPs had a superparamagnetic property and efficient accumulation kinetics under an external magnetic field. Moreover, the magnetic field-exposed DL MNPs show quantitative accumulation, whereas Fe3O4 NPs single-layered silica nanoparticles (SL MNPs) and silica-coated Fe3O4 NPs produced a saturated plateau under full recovery of the NPs. DL MNPs are promising nanomaterials with great potential to separate and analyze biomolecules.
Keywords: IRON-OXIDE NANOPARTICLES; HOLLOW SPHERES; DRUG-DELIVERY; CELL-SEPARATION; QUANTUM DOTS; NANOCLUSTERS